General adaptation syndrome and its applications in Sport Training - Verkhoshansky, N. (Central Virginia Sport Performance, 2012)
The General Adaptation Syndrome (GAS) has been looked upon as the benchmark for understanding the stress response to training, thus determining the "adaptations" that will be seen in the athletes. On the base of the latest research on GAS, never published in the West, this presentation shows a new and innovative point of view on GAS, areas that coaches can observe, and how this theory has been adapted sense its inception.